Theoretical design and exploration of novel high energy density materials based on silicon - Xi, Hong-Wei (2020)
Si-based high energy density materials (HEDMs) have been theoretically studied based on density functional theory and ab initio molecular dynamics simulation. These HEDM compounds have a unique fused-heterocyclic structure centered at Si. A new theoretical technique was used to predict crystal density of HEDMs. It takes into considerations crystal packing and intermolecular interactions. The calculation predicts that the new class of HEDMs can have significantly higher densities than classical energetic materials (from 2.05 to 2.30 g/cm3). Their heats of formation are significantly higher than that of classical energetic materials. In addition, electronic structures of the chemical bonds within these HEDM compounds were theoretically determined and discussed in relation to sensitivity and stability of the compounds. The present research discovers that creatively designed substitution of C by Si in HEDMs can potentially lead to promising candidates with high performance, moderately high thermal stability, and low-impact sensitivity.